2018
DOI: 10.5713/ajas.18.0059
|View full text |Cite
|
Sign up to set email alerts
|

Oil supplementation improved growth and diet digestibility in goat and sheep fed fattening diet

Abstract: The findings of this study suggested that sheep performed better than goats when fed fattening diet and oil supplementation at the inclusion rate of 4% provides a viable option to significantly enhance growth performance and FCR in fattening sheep and goats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
1
7
2
Order By: Relevance
“…However, garlic oil had no effect on ash intake. This result on ash is in consistent with previously published reports where oil supplementation in goats' diet has no effect on mineral intake [20].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, garlic oil had no effect on ash intake. This result on ash is in consistent with previously published reports where oil supplementation in goats' diet has no effect on mineral intake [20].…”
Section: Discussionsupporting
confidence: 94%
“…The progressive increase in the digestibility of DM, CP, crude fibre (CF) and neutral detergent fibre (NDF) up to 30 g (3%) of garlic oil supplementation in this study could possibly suggest that the rumen microbes had adapted to that levels of linolenic and lauric acids in garlic oil which resulted in reduction of protozoa, leading to a higher population of bacteria, hence increased digestibility of nutrients. This contradicts the reports of Candyrine et al [20] that 4% linseed oil supplementation in diets of goats improved digestibility. This inconsistency could be due to the type of oil used in the different studies which are made up of different composition of fatty acids.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Candyrine et al reported that 4% oil supplementation to diet significantly enhanced the growth performance in fattening sheep and goats [ 22 ]. In the current study, compared with the CON group, the dietary flaxseed oil supplementation significantly increased the FBW and BWG, which agrees with the above report.…”
Section: Discussionmentioning
confidence: 99%
“…The quality feed is very necessary to generate the sheep body weight, which is expected. The expected body weight and average daily gain (ADG) from sheep fattening should be high [1]. However, the high body weight was not always generated a good quality of the carcass, because high fat carcass will cause loss to the producer [2].…”
Section: Introductionmentioning
confidence: 99%